2009
DOI: 10.1097/cad.0b013e3283182913
|View full text |Cite
|
Sign up to set email alerts
|

Rhein lysinate suppresses the growth of breast cancer cells and potentiates the inhibitory effect of Taxol in athymic mice

Abstract: Earlier studies have shown that rhein, one of the major bioactive constituents of the rhizome of rhubarb, inhibits the proliferation of various human cancer cells. However, because of its water insolubility, the antitumor efficacy of rhein is limited in vivo. In this study, we studied the antitumor activity of rhein lysinate (the salt of rhein and lysine and easily dissolving in water) and its mechanism. Inhibition of breast cancer cell proliferation was determined by MTT assay and the mechanism of action of r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
40
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(43 citation statements)
references
References 24 publications
2
40
1
Order By: Relevance
“…The increase of HeLa cell growth inhibition by the combination of RHL with U0126 was accompanied by the enhancement of the activation of caspase-3/7 and PARP, suggesting that ERK is involved in regulating cell survival. The finding that RHL inhibited ERK activation was shown in another study using human mammary epithelial MCF cells (9). However, in our study, the activation of ERK was increased following RHL treatment in HeLa cells.…”
Section: Discussioncontrasting
confidence: 54%
See 2 more Smart Citations
“…The increase of HeLa cell growth inhibition by the combination of RHL with U0126 was accompanied by the enhancement of the activation of caspase-3/7 and PARP, suggesting that ERK is involved in regulating cell survival. The finding that RHL inhibited ERK activation was shown in another study using human mammary epithelial MCF cells (9). However, in our study, the activation of ERK was increased following RHL treatment in HeLa cells.…”
Section: Discussioncontrasting
confidence: 54%
“…Our previous study showed that RHL exhibits anti-cancer activity in breast and ovarian cancer, and hepatocellular carcinoma in vivo and in vitro (9)(10)(11). In the present study, RHL was shown to inhibit the growth of human cervical cancer cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In previous studies, Rhein was found to have a variety of bioactivities, such as inhibiting IL-1 induced chondrocyte activation [9] , decreasing hypertrophy in mesangial cells [10] , inhibiting tumor cell proliferation, and inducing tumor cell apoptosis [11] . In our previous study, we also found that a dose of more than 20 µmol/L RHL could inhibit tumor cell proliferation, and it acted synergistically with Taxol when combined, both in vitro and in vivo [12] . However, less than 20 µmol/L RHL can also improve cell viability.…”
Section: Introductionmentioning
confidence: 99%
“…The anti-angiogenic property of rhein has been characterized in a zebrafish model (97,98). Interestingly, rhein lysinate showed a synergistic increase in the anti-tumor activity of Taxol in mice (185,186). It has also been shown to influence cell growth and apoptosis in several human cancer cell lines such as cervical cancer Ca Ski (120), colon adenocarcinoma CaCo-2 (245), glioma U-373MG (74), hepatocellular carcinoma BEL-7402 (265), hepatoblastoma HepG2 (146), lung cancer A549 (108), promyelocytic leukemia HL-60 (181), and human tongue SSC-4 cancer cell lines (42,150).…”
Section: The Inhibitory Mechanisms Of Natural Compounds Against Npc Smentioning
confidence: 99%